Like no other - LaMarche, Una (Razorbill, an imprint of Penguin Group (USA), 2014)
Though their relationship is strictly forbidden, Devorah and Jax arrange secret meetings and risk everything to be together. But how far can they possibly go? Just how much are they willing to give up?